Song of a captive bird [large type] : a novel - Darznik, Jasmin, 1973- (Thorndike Press, a part of Gale, a Cengage Company, 2018)
"All through her childhood in Tehran, Forugh Farrokhzad is told that Persian daughters should be quiet and modest. She is taught only to obey, but she always finds ways to rebel--gossiping with her sister among the fragrant roses of her mother's walled garden, venturing to the forbidden rooftop to roughhouse with her three brothers, writing poems to impress her strict, disapproving father, and sneaking out to flirt with a teenage paramour over café glacé. During the summer of 1950, Forugh's passion for poetry takes flight--and tradition seeks to clip her wings." --